Defining the Histologic Support Structures of the Nasal Ala and Soft Triangle: Toward Understanding the Cause of Iatrogenic Alar Retraction. Issue 3 (September 2020) - Dowlatshahi, A. Samandar; Constantian, Mark B.; Deng, April; Fudem, Gary
Abstract : Background: As rhinoplasty techniques have evolved to more extensive dissections, the incidence of iatrogenic deformities, such as alar rim retraction, has risen. Its mechanism is presently unknown. This study examined the microscopic anatomy of the nasal ala to define architectural support elements at the histologic level to determine why rhinoplasty dissection creates such deformities. Methods: Eight cadaveric noses were harvested and sectioned through the soft triangle and ala. Various tissue stains were performed. Slides were examined using light microscopy. Anatomical features pertaining to cartilage, skin, mucosa, elastic fibers, and muscle were documented. Results: Four male and four female noses were sectioned. The median cadaver age was 64 years (range, 47 to 83 years). On Elastica van Gieson stain, distinct elastic fibers span from the vestibular lining to the caudal margin of the lower lateral cartilage, and from the caudal edge of the lower lateral cartilage to the external alar skin. In the nasal ala midsection, trichrome stains reveal that skeletal muscle is located far beyond the lower lateral cartilage, close to the free alar margin. The soft triangle shows a distinct microanatomical structure, with heavy longitudinal condensations of elastin. These histologic findings have not been previously reported. Conclusions: A distinct anatomical alar wall endoskeleton has been identified. It is obligatorily disrupted by specific rhinoplasty maneuvers when dissection is carried out over the lateral crura and into areas without cartilaginous support. This microanatomy may explain factors that contribute to postoperative alar wall retraction. Leaving this area undisturbed or performing adjunctive measures with rhinoplasty can provide structural support to the external valves, thus minimizing the risk of deformity.